Effects of Organizational Formalization on Alienation Among Professionals and Nonprofessionals - Podsakoff, Philip M.; Williams, Larry J.; Todor, William D. (Academy of Management Journal, 1986)
In this article the authors replicate a study that was conducted to examine the effects that organizational formalization had on the feelings of alienation of professional employees. The authors of the present study add the wrinkle of also examining non-professional employees in their research. They note that while the original study found that increased formalization did not directly affect feelings of alienation it did increase role conflict, decrease role ambiguity and enhanced organizational identification. They discuss how formalization can have conflicting effects in the areas of role stress and alienation and are interested if the same results can be obtained among nonprofessional employees as well.